Potential impact of the leaf‐cutting ant Acromyrmex lobicornis on conifer plantations in northern Patagonia, Argentina - Pérez, Silvia Paola; Corley, Juan Carlos; Farji Brener, Alejandro Gustavo (Wiley, 2019)
The economic losses associated with crop damage by invasive pests can be minimized by recognizing their potential impact before they spread into new areas or crops. We experimentally evaluated the preferences of the leaf‐cutting ant Acromyrmex lobicornis (Hymenoptera: Formicidae) for the most common conifer species commercially planted in northern Patagonia, Argentina. The areas of potential forest interest in this region and the geographical range of this ant overlap. We performed field preference tests and monitored the level of ant herbivory on planted conifer seedlings next to nests. Acromyrmex lobicornis preferred some conifer species and avoided foraging on others. Pseudotsuga menziesii and Austrocedrus chilensis were the less preferred species, Pinus ponderosa and Pinus contorta were the most preferred by A. lobicornis. The item mostly selected by ants was young needles from P. contorta. This species was also the pine mostly defoliated. Seedlings without ant‐exclusion showed a mean±SE of 60±5% defoliation during the sampling period. Pinus ponderosa was less defoliated; control seedlings showed a mean±SE of 8.5±1% of leaf damage in the sampling period. The present study shows how the use of simple field tests of leaf‐cutting ant preferences could allow an improved selection of appropriate conifer species for future plantations in areas where leaf‐cutting ants are present.